Overview of Nutritional Status of Pregnant Women with Preeclampsia: Case Study in Aru Islands Regency, Dobo City, Southeast Maluku - Rifatolistia Tampubolon; Hapsari Probowati; Judith Devi Manutilaa (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2021)
Background: Preeclampsia is a syndrome in terms of hypertension after 20-week pregnancy referring to a pregnant woman that previously had normal blood pressure, followed by having hypertension, proteinuria, edema and generally occurs in the third trimester of pregnancy. Preeclampsia is one of five main causes of maternal mortality up to 12% in the world as well. Objective: This study was conducted to describe nutritional status of pregnant women with preeclampsia in Aru Islands Regency, Dobo City, Southeast Maluku. Methodology: This study used mix methods, namely, quantitative and qualitative research with Case Study design. Qualitative research was to determine nutritional status of pregnant women with preeclampsia and quantitative research was to record nutrition intake of pregnant women and measure nutritional status of pregnant women with preeclampsia. Results & Discussion: Characteristics of participants with preeclampsia were more than 27 years old, worked as housewife that could be one of stress triggers and had some risk to increase preeclampsia cases because of stress that caused blood pressure increase. Preeclampsia was detected in pregnancy term of participants about 20-30 weeks according to Maternal and Child Health data. Preeclampsia risk was doubly by every increase in body weight (5-7 kg). Participants had body weight increase ranging from 8-25 kg which caused preeclampsia risk increase. Parameters of recommended dietary allowances of pregnant women including energy excess, protein deficit, fat excess, calcium and zinc deficiency were secondary factor of preeclampsia risk increase in Aru Islands Regency, Dobo City, Southeast Maluku.